Construção de uma sequência didática para o ensino de ecologia com enfoque CTSA: A visão de docentes do ensino superior - Rosa, Isabela Santos Correia (2017)
This paper presents part of a master&39;s thesis on the possibilities of insertion of the STSE (Science, Technology, Society and Environment) in ecology classes in basic education. One of its results refers to the lack of support material as the main difficulty pointed out by the teachers, which motivated the elaboration of a proposal of a didactic sequence to approach this subject in the STSE perspective. Then, the material elaborated was evaluated both by higher education teachers, specialists in the Education and Ecology areas, and teachers from the state network of three municipalities of Sergipe: Lagarto, Salgado and Boquim. In this essay, the process of evaluation of this material by higher education teachers is presented. For these teachers the didactic sequence elaborated represents a good teaching strategy and should contribute to the formation of critical citizens.